Evidential value of the hospital record in clinical decision making. Issue 6174 (19th May 1979) - Card, W I; Sircus, W; Smith, A N
Abstract : A simulated retrospective exercise in the diagnosis and management of 53 readmissions to a gastrointestinal unit was undertaken by two consultants. Diagnosis of the illness at readmission was made on evidence sought from a referee, who also supplied, on request, items of relevant evidence from the past medical record. Patient management was agreed from these sources. For each item of evidence the evidential weight, the irrecoverability, and the expected benefit accruing to the patient of its availability was calculated. It was concluded that the evidence worth recording in the event of subsequent hospital admission could be largely specified for each diagnosis and each operation. It would be brief and could be numerically coded.